Usulan Strategi Pengembangan UMKM Keripik Cabe Melur Menggunakan Metode Business Model Canvas - Armanda, Erwin; Anwardi, Anwardi; Kusumanto, Ismu; Yola, Melfa; Harpito, Harpito (Universitas Al Azhar Indonesia, 2025)
UMKM Keripik Cabe Melur is a business operating in the snack food sector located in Dumai City. UMKM Keripik Cabe Melur continues to develop in terms of equipment which now uses machines but in running its business it experiences problems with sales not reaching targets. This research aims to analyze the business model description and propose alternative strategies for developing UMKM Keripik Cabe Melur. This research uses the Business Model Canvas method and SWOT Analysis method which will provide strategy proposals starting with carrying out BMC analysis, IFE matrix, IFE Matrix, IE matrix, SWOT matrix analysis and eventually proposed a feasible BMC. Alternative strategies proposed are identifying most potential customer segments (need to reach online resellers), value propositions (increasing purchasing media on social media and e-commerce and being able to increase production according to demand), channels (marketing and promotion via social media, gift shops and e-commerce such as Tik Tok shop, Shopee, Lazada, Instagram and Facebook with special prices), key activities (Sales and promotions via social media and e-commerce with attractive posters), Key resources (requires a smartphone to support sales and promotions on social media and e-commerce), Key partners (cooperating with goods delivery services) and cost structure (incurring promotion and internet service costs).Keywords - Business Model Canvas Method, Development Strategy, Keripik Cabe, UMKM, SWOT Method.